International legal regulation of oil and gas activities in the Arctic - N. Yu. Molchakov; O. V. Glikman (Сравнительная политика, 2022)
The purpose of the research is to identify and analyze international legal norms applicable to the exploration and exploitation of oil and gas resources in the Arctic, as well as trends of their development. The objectives of the research include the analysis of international legal norms that determine the status of the Arctic, legal features arising from differences in the status of some Arctic territories, differences in the approaches of Arctic and non-Arctic states, the European Union, as well as the identification of legal vectors of international legal regulation that are significant for oil and gas activities in the Arctic.The article highlights the trends in the development of international legal regulation of general priority issues and sectoral aspects of activities in the Arctic. The authors revealed the meaning and features of multilateral and bilateral international treaties of the Russian Federation, advisory acts of the Arctic Council applicable to oil and gas activities in the Arctic.The authors identified contradictions between the oil and gas aspects of the Arctic concept of the European Union of 2021 and jurisdictional and natural resource principles and rules provided for in international treaties and customs. The authors formulated proposals that can be used by Russia as international legal counterarguments proving the illegality of the EU’s stated goal to prohibit oil and gas production in the Arctic.